The JAK2/STAT5 signaling pathway as a potential therapeutic target in canine mastocytoma - Keller, Alexandra (Vet Comp Oncol, 2017)
BACKGROUND: Mastocytoma are frequently diagnosed cutaneous neoplasms in dogs. In non-resectable mastocytoma patients, novel targeted drugs are often applied. The transcription factor STAT5 has been implicated in the survival of human neoplastic mast cells (MC). Our study evaluated the JAK2/STAT5 pathway as a novel target in canine mastocytoma. MATERIALS AND METHODS: We employed inhibitors of JAK2 (R763, TG101348, AZD1480, ruxolitinib) and STAT5 (pimozide, piceatannol) and evaluated their effects on 2 mastocytoma cell lines, C2 and NI-1. RESULTS: Activated JAK2 and STAT5 were detected in both cell lines. The drugs applied were found to inhibit proliferation and survival in these cells with the following rank-order of potency: R763 > TG101348 > AZD1480 > pimozide > ruxolitinib > piceatannol. Moreover, synergistic anti-neoplastic effects were obtained by combining pimozide with KIT-targeting drugs (toceranib, masitinib, nilotinib, midostaurin) in NI-1 cells. CONCLUSION: The JAK2/STAT5 pathway is a novel potential target of therapy in canine mastocytoma.